Next-Gen Bio-Implant Ecosystem for Secure Living: Real-Time Medical Access and Criminal Monitoring - S, Arun (Journal of Advanced Research in Electronics Engineering and Technology; Vol 12 No 1&2 (2025): Journal of Advanced Research in Electronics Engineering and Technology, 2025)
Bio-implant technology is revolutionising the fields of security, healthcare, and automation. This research investigates the dual-frequency NExT RFID + NFC Chip—which combines a 13.56 MHz NTAG216 (ISO14443A) and a 125 kHz T5577 (EM41xx/HID compatible) component—for advanced multi-factor authentication (MFA), IoT integration, criminal tracking, and emergency medical data access. By conducting extensive experimental evaluations and testing, this study assesses the technical feasibility, performance, and security implications of bio-implant technology. Detailed comparative analyses, real-world use case evaluations, and forward-looking discussions on regulatory and ethical issues are presented.